The mortality rate among patients with acute upper GI bleeding (with/without EGD) at Aleppo University Hospital: A retrospective study. (November 2021) - Aljarad, Ziad; Mobayed, Bashir Badawi
Abstract: Background: acute upper gastrointestinal bleeding (UGIB) is a common medical condition that results in substantial morbidity, mortality, and medical care cost. The mortality rate for patients with acute upper gastrointestinal (GI) bleeding is 5–10%, and it has not changed much since 1945, despite the development in medicines, endoscopy, intensive care units (ICU), and surgical management. We conduct this study to observe some of the factors that predict death in these patients. Materials and methods: The Study was conducted at the Internal Medicine Department, Digestive Division, Aleppo University Hospital, between July 2018 and June 2020. The study included all patients with acute upper GI bleeding who were admitted to the digestive division during the study period, or who were admitted by other departments requesting an upper GI endoscopy. Results: This study involved 234 patients, 137 males (58.55%), 97 females (41.45%). The patients' ages ranged between 17 and 81 years old, and the mean age value ± standard deviation was 57.15 ± 22.89 years old. The number of deaths reached 22, at a rate of 9.40%, 14 male deaths (10.22%), 8 female deaths (8.25%). Conclusions: in this study we found a moderate inverse relationship between the hemoglobin value at admission and the incidence of death; the lower the hemoglobin value at admission, the higher the probability of patient's death. Also, there is a very significant direct relationship between the number of blood units transfused and the incidence of death, noting that all patients who died had received blood transfusions. Finally, we found a moderate inverse relationship between the arterial blood pressure value at admission and the incidence of death. Highlights: Acute upper gastrointestinal bleeding (UGIB) is a common medical condition that results in substantial morbidity, mortality, and medical care cost. We found an inverse association of average severity between the hemoglobin value at admission and the incidence of death. There is a very significant positive correlation between the number of blood units transfused and the incidence of death, and a negative association of moderate severity between the arterial blood pressure value at admission and the incidence of death. Upper gastrointestinal bleeding is a life-threatening condition that requires urgent admission and prompt intervention via endoscopy if needed.